On the evaluation of synthetic and natural ilmenite using syngas as fuel in chemical-looping combustion (CLC) - Azis, Muhammad Mufti; Jerndal, Erik; Leion, Henrik; Mattisson, Tobias; Lyngfelt, Anders (Chemical engineering research & design, 2010)
Chemical-looping combustion (CLC) is a combustion technique where the CO 2 produced is inherently separated from the rest of the flue gases with a considerably low energy penalty. For this reason, CLC has emerged as one of the more attractive options to capture CO 2 from fossil fuel combustion. When applying CLC with solid fuels, the use of a low cost oxygen carrier is highly important, and one such low cost oxygen carrier is the mineral ilmenite. The current work investigates the reactivity of several ilmenites, some which are synthetically produced by freeze granulation and two natural minerals, one Norwegian ilmenite and one South African ilmenite. A laboratory fluidized bed reactor made of quartz was used to simulate a two reactor CLC system by alternating the reduction and oxidation phase. The fuel was syngas containing 50% CO and 50% H 2. A mixture of 6 g of ilmenite with 9 g inert quartz of diameter 125–180 μm was exposed to a flow of 900 mL n/min syngas in the reduction phase. During the oxidation phase, a 900 mL n/min flow of 10% O 2 diluted in N 2 was used. The experimental results showed that all ilmenites give higher conversion of H 2 than of CO. Generally, synthetic ilmenites have better CO and H 2 conversion than natural ilmenites and synthetic ilmenites prepared with an excess of Fe generally showed higher total conversion of CO than synthetic ilmenites with an excess of Ti. Most synthetic ilmenites and the Norwegian ilmenite showed good fluidization properties during the experiments. However, for two of the synthetically produced materials, and for the South African ilmenite, particle agglomerations were visible at the end of the experiment.